Implementation of TPACK-Oriented Thematic Learning at SD Muhammadiyah 11 Mangkuyudan Surakarta - Rahayuningtyas, Asri; Rohmah, Warotur; Maryadi, Maryadi (CV. Rayyan Dwi Bharata, 2023)
Teachers are the main factor and determinant of the success of learning and efforts to update the quality of education. The development of the times requires teachers to be able to carry out learning using technology. TPACK (Technological Paedagogical and Content Knowledge) is the teacher's ability to combine strategies, media, materials, and evaluation of learning using technology. The TPACK ability must be owned by a teacher because it can affect the way material is delivered to students. Muhammdiyah 11 Mangkuyudan Elementary School is one of the private schools in Surakarta City, to be precise, in Laweyan District. Teachers who teach at these schools have good competence in their fields. This study aims to describe the implementation of TPACK-oriented Thematic learning at SD Muhammadiyah 11 Mangkuyudan Surakarta. This research uses a qualitative type of research, the data obtained will show objectively the TPACK abilities of SD Muhammdiyah 11 Mangkuyudan Surakarta teachers for the 2020/2021 academic year. The results showed that: Class teacher TPACK ability in thematic learning at Muhammadiyah 11 Mangkuyudan Elementary School was included in the sufficient category with a percentage of 58.69%. If viewed per aspect then: CK is in the very good category with a percentage of 85.65%, PK is in the sufficient category with a percentage of 54.22%, Kindergarten is in the adequate category with a percentage of 57.64%, PCK is in the good category with a percentage of 73.60%, TCK is in the adequate category with a percentage of 53.83%, and TPK is in the unfavorable category with a percentage of 46.12%